FINTECH PAYMENT ABILITY FOR MSME ACTIVITIES OF THE BABY BOOMERS GENERATION IN SOUTH TANGERANG CITY - Shalsa Azzahra; Sri Indah Nikensari; Saparuddin Mukhtar (CURRENT ADVANCED RESEARCH ON SHARIA FINANCE AND ECONOMIC WORLDWIDE, 2022)
Advances in technology in the financial sector, namely fintech payments in the current digital era, can be a challenge to adapt in everyday life. And it is undeniable that the generation that grew up with technology has very different expectations and experiences in using digital media than previous generations. This study aims to determine the effect of digital economic literacy and financial inclusion on the ability to use fintech payments through financial inclusion for the MSMEs of the baby boomers generation based on valid data. Data collection was carried out in this study using quantitative techniques with data analysis techniques Path Analysis through questionnaires. The number of samples studied were 160 SMEs of the baby boomers generation in South Tangerang City in 2022. The research variable data was in the form of primary data consisting of the ability to use fintech payments (Y), digital economic literacy (X1) and financial inclusion (X2). The results of the study show that digital economic literacy has a positive effect on the ability to use fintech payments; financial inclusion has a positive effect on the ability to use fintech payments; digital economic literacy has an indirect effect on the ability to use fintech payments through financial inclusion.